Preexisting Oral Anticoagulant Therapy Ameliorates Prognosis in Hospitalized COVID-19 Patients - Iaccarino, Guido; Grassi, Guido; Borghi, Claudio; Grassi, Davide; Mancusi, Costantino; Muiesan, Maria Lorenza; Salvetti, Massimo; Volpe, Massimo; Ferri, Claudio (Frontiers in Cardiovascular Medicine, 2021)
Objective: Altered coagulation parameters in COVID-19 patients associates with poor prognosis. We tested whether COVID-19 patients on chronic oral anticoagulants (cOACs) for thromboembolisms prophylaxis could receive protection from developing more severe phenotypes of the disease. Approach and Results: We interrogated the database of the SARS-RAS study (Clinicaltrials.gov: NCT04331574), a cross-sectional observational multi center nationwide survey in Italy designed by the Italian Society of Hypertension. The database counts 2377 charts of Italian COVID-19 patients in 26 hospitals. We calculated the Charlson Comorbidity Index (CCI), which associates with death in COVID-19 patients. In our population (n=2377, age 68,2plus minus0,4 years, CCI: 3,04plus minus0,04) we confirm that CCI associates with increased mortality (OR: 1,756 [1,628-1,894]), admission to intensive care units (ICU; OR: 1,074 [1,017-1,134]) and combined hard events (CHE; OR: 1,277 [1,215-1,342]). 125 patients were on cOACs (age: 79,3plus minus0,9 years, CCI: 4.35plus minus0,13); despite the higher CCI, cOACs patients presented with a lower risk of accesses to ICU (OR 0.469 [0.250-0.880]), but not of death (OR: 1.306 [0.78-2.188] or CHE (OR: 0,843 [0.541-1.312]). In a multivariable logistic regression, cOACs confirmed its protective effect on ICU access and CHE. The CCI remains the most important risk factor for ICU access, death and CHE. Conclusions: our data support a mechanism for continuation of cOAC therapy also after hospital admission for those patients that are on chronic treatment. We propose the prophylactic use of direct cOACs in patients with elevated CCI score at the time of COVID-19 pandemia, even in absence of other risk of thromboembolism.